EJE AWARD 2020: Signalling by G protein-coupled receptors: why space and time matter. Issue 2 (February 2021) - Calebiro, Davide
Abstract : G protein-coupled receptors (GPCRs) are the largest family of membrane receptors and major drug targets. They play a fundamental role in the endocrine system, where they mediate the effects of several hormones and neurotransmitters. As a result, alterations of GPCR signalling are a major cause of endocrine disorders such as congenital hypothyroidism or Cushing's syndrome. My group develops innovative optical methods such as fluorescence resonance energy transfer (FRET) and single-molecule microscopy, which allow us to investigate GPCR signalling in living cells with unprecedented spatiotemporal resolution. Using this innovative approach, we have contributed to elucidate some long-debated questions about the mechanisms of GPCR signalling and their involvement in human disease. Among other findings, these studies have led to the unexpected discovery that GPCRs are not only signalling at the cell surface, as previously assumed, but also at various intracellular sites. This has important implications to understand how hormones and neurotransmitters produce specific responses in our cells and might pave the way to innovative treatments for common diseases like diabetes or heart failure.